1/5 (c) since it goes up only one and then over 5
Answer:
x = – ⅓
Step-by-step explanation:
The solution to the expression can be obtained as follow:
–3.1x + 7 – 7.4x = 1.5x – 6(x – 3/2)
Clear bracket
–3.1x + 7 – 7.4x = 1.5x – 6x + 9
–3.1x – 7.4x + 7 = –4.5x + 9
–10.5x + 7 = –4.5x + 9
Collect like terms
–10.5x + 4.5x = 9 – 7
–6x = 2
Divide both side by –6
x = 2 / –6
x = – ⅓
Thus, the solution to the equation is –⅓
Answer:
x = 1?
Step-by-step explanation:
I think functions are basically just variables but extra so they both act the same. I'm not 100% sure but I Think
if f(x) = -5x + 1 when f(x) = 6,
replace f(x) with 6 so,
6 = 5x + 1
1 - 6 = 5x + 1 - 1
(subtract one on both sides to isolate the variable)
5 = 5x
5/5 = 5x/5
(to Actually isolate the variable lol
1 = x or x = 1
I believe is the answer? please comment if I'm wrong
*I WAS TOLD MY THOUGHT PROCESS IS WRONG ANYONE WHO SEES THIS PLEASE DISREGARD
It should be 5√3
Because 25 x 3 = 75
√25=5 so u bring that out and keep the 3 in because it’s a prime number
I believe it’s 16/21 but I’m not sure.